Nutritional adequacy of triticale for finishing swine - Allee, G.L.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
An experiment involving 81 finishing pigs was conducted to determine the nutritional adequacy of triticale for finishing swine. Pigs fed triticale alone gained significantly (P<.05) slower than pigs fed any other diets. Adding 0.1% L-lysine to triticale significantly (P<.05) increased daily gain. There were no significant differences in daily gain, feed intake, or feed:gain ratio between pigs fed triticale + lysine, triticale + soybean meal, milo + soybean meal or wheat + soybean meal. Differences in backfat thickness, loin-eye area, length or percentage of lean cuts in the carcass were not significant. Lysine is the first limiting amino acid in triticale for finishing swine. The lysine in triticale may not be totally available to pigs.
Swine Industry Day 1972 is known as Swine Day 1972
Keywords: Swine; Triticale; Finishing pigs; Lysine; Milo; Feed/gain